Blockchain technology for smart grids : implementation, management and security - Gururaj, H. L., 1988-; Ravi Kumar, V.; Flammini, Francesco; Lin, Hong; B, Goutham; B. R., Sunil Kumar; Sivapragash, C. (IET energy engineering series ;, 2022)
Smart grids with distributed clean energy generation, storage and prosumers are the future of energy systems. They need two-way digital communication between multiple customers and suppliers of energy, to produce, buy and sell electricity to the grid at small scales. These arrangements need a system that maintains, checks, and registers information about transactions. Blockchain technology is able to handle these requirements with smart contracts, peer-to-peer energy trading and immutable transactions. A blockchain is a digital ledger of transactions that can be accessed across the entire network of computer systems. Combined with sensors to track energy flows, blockchain can enable the smart grid. After an introduction to blockchain, chapters cover integration with IoT, IoT- and blockchain-enabled smart grids, use of sensors, security and privacy, use of machine and deep learning, energy storage and transaction, as well as use of cryptocurrencies for transactions. Written by an international team with the necessary multi-disciplinarity, this work for researchers in power systems as well as economists with related interests covers the use of blockchain technology for smart grids.